Challenges of time metrology - Dimarcq, N. (2025)
In close cooperation with the BIPM Time department, the Consultative Committee for Time and Frequency (CCTF) is working on "hot topics" corresponding to current and future challenges of time and frequency metrology. The presentation will provide an overview of the CCTF activities and will address especially the following topics: - Redefinition of the second - Since 1967, the definition of the second is based on a transition of the caesium atom. The best accuracy of primary frequency standards realizing the second is today at 10-16 but, in the last 10 years, optical frequency standards demonstrated a relative frequency accuracy of 10-18. The debate on the possible options for the redefinition of the second is thus very much alive and mandatory criteria (on optical frequency standards and their contribution to international time scales, on time & frequency transfer techniques, etc.) to be fulfilled before the redefinition is fixed. - Continuous UTC - The CCTF is strongly involved in an important evolution of the international time standard UTC to enlarge the maximum limit of UTC-UT1 beyond one second, in order to ensure the continuity of UTC for at least 100 years. This new process is expected to come into force in or before 2035, with a current evaluation of the probability for the occurrence of a negative leap second in the next decade, leading to an exceptional situation that has never been experimented before.. - Promotion of the mutual benefit of UTC and GNSS - The aim is to improve the collaboration with the providers and users of GNSS highlighting the mutual benefits for navigation and time metrology in applications such as time transfer, interoperability, and traceability to UTC through the GNSS broadcast information. - Reference time for the Moon Current discussions and activities aim at defining a Lunar reference time, traceable to UTC, to ensure the interoperability of the systems for Positioning, Navigation and Timing (PNT) in a cislunar environment.